Optimization of reinforcement ratio and stirring speed on mechanical properties of Al-TiB2-B4C hybrid composite using Taguchi – grey relational analysis - Sheetal Soni; Piyush Gohil (Materials Research Express)
The aim of the research is to optimise percentage ratio of hybrid reinforcements and stirring speed to maximize the mechanical properties of the hybrid composite by applying Taguchi analysis and grey relational analysis. The matrix material employed in this study is Al 7075, while boron carbide (B _4 C) and titanium diboride (TiB _2 ) serve as the reinforcement materials. The hybrid metal matrix composite is produced via the stir casting method. For experimental design Taguchi L9 orthogonal array was adopted, with the weight percentage of the reinforcement materials and stirring speed identified as experimental factors. The specified levels of weight percentage for the reinforcements B _4 C and TiB _2 were established at 3%, 6%, and 9%. The incorporation of both hard ceramic particles, B _4 C and TiB _2 plays a significant role in improving the mechanical properties of the hybrid composite. The highest tensile strength, hardness and flexural strength achieved is 203.72MPa, 129.2 BHN and 369 MPa respectively for highest percentage ratio of both the reinforcements i.e. Al/9% B _4 C/ 9% TiB _2 and for 600 rpm stirring speed. The mechanical properties analysed as response parameters consist of tensile strength, hardness, impact strength, and flexural strength. The Taguchi analysis, particularly the signal-to-noise (S/N) ratio evaluation, reveals that the percentage weight of TiB _2 is the predominant factor affecting tensile strength. In contrast, the percentage weight of B _4 C significantly influences both hardness and flexural strength, while stirring speed is the most critical parameter for impact strength. The optimal parameters identified for maximizing tensile strength, hardness, and flexural strength are 9% B _4 C, 9% TiB _2 , and a stirring speed of 600 rpm. Multi-objective optimization employing grey relational analysis is performed to maximise the mechanical properties. The highest grey relational grade was attained in experiment number 9, which is having parameter values 9% of B _4 C, 9% of TiB _2 and stirring speed of 600 rpm. The integration of Taguchi and grey relational analysis provides a robust optimization framework, offering a systematic methodology that enhances the understanding of parameters and enables the development of high-performance HMMCs tailored for engineering applications characterized by high significant demands.